2011
DOI: 10.7150/ijms.8.558
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Epithelioid Hemangioendothelioma Involving the Same Lower Extremity: A Case Report and Review of Literature

Abstract: Epithelioid hemangioendothelioma (EH) is an uncommon low-grade malignant soft-tissue tumor; no case has been previously reported where multicentric epithelioid hemangioendothelioma occurred in the same lower extremity at different sites. We report a case involving the common peroneal nerve and subsequently the long bone and the short bones of the same lower extremity, and also review the literature. After establishing case of several lesions, we reviewed the histopathology properly and followed up the patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…This results in an unpredictable, yet oftentimes, indolent clinical course, and patients can survive for decades even with Fig. 1 Axial, non-contrast, CT scan demonstrating a complex mass filling the right maxillary sinus with erosion of the medial (arrow) and posterior maxillary sinus walls (asterisk) multi-organ disease [11,12]. Mentzel et al [12] noted 20 % of tumors metastasized and 17 % of patients died in their study.…”
Section: Histologymentioning
confidence: 99%
“…This results in an unpredictable, yet oftentimes, indolent clinical course, and patients can survive for decades even with Fig. 1 Axial, non-contrast, CT scan demonstrating a complex mass filling the right maxillary sinus with erosion of the medial (arrow) and posterior maxillary sinus walls (asterisk) multi-organ disease [11,12]. Mentzel et al [12] noted 20 % of tumors metastasized and 17 % of patients died in their study.…”
Section: Histologymentioning
confidence: 99%
“…Mainly located in the long tubular bones of the lower extremities and pelvis, the tumor is rarely found in the upper extremities and flat bones (5)(6)(7)(8)(9). Therefore, the formation of a definitive diagnosis of EH is difficult and the tumor is easily misdiagnosed.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have indicated that multifocal EH may exhibit a better prognosis than unifocal EH, however, the pathogenesis remains controversial and the number of cases reported is limited (8,16). Various mechanisms have been described, including metastatic spread, malignant transformation and multifocal formation.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some authors began to believe the hypothesis that EHE does not represent a distinct entity, but rather is an intermediate state of endothelial dedifferentiation with a highly variable and unpredictable prognosis [5]. …”
Section: Introductionmentioning
confidence: 99%